2002
DOI: 10.1126/science.1070955
|View full text |Cite
|
Sign up to set email alerts
|

Explaining the Latitudinal Distribution of Sunspots with Deep Meridional Flow

Abstract: Sunspots, dark magnetic regions occurring at low latitudes on the Sun's surface, are tracers of the magnetic field generated by the dynamo mechanism. Recent solar dynamo models, which use the helioseismically determined solar rotation, indicate that sunspots should form at high latitudes, contrary to observations. We present a dynamo model with the correct latitudinal distribution of sunspots and demonstrate that this requires a meridional flow of material that penetrates deeper than hitherto believed, into th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
236
3
6

Year Published

2004
2004
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 239 publications
(249 citation statements)
references
References 28 publications
4
236
3
6
Order By: Relevance
“…With the helioseismically determined rotation profile, this seems unlikely and it may well be that the toroidal field is actually generated at the high latitude, even though it is not allowed to erupt there. Recent calculations by Guerrero & Muñoz (2004) support the findings of Nandy & Choudhuri (2002).…”
Section: Introductionsupporting
confidence: 70%
See 2 more Smart Citations
“…With the helioseismically determined rotation profile, this seems unlikely and it may well be that the toroidal field is actually generated at the high latitude, even though it is not allowed to erupt there. Recent calculations by Guerrero & Muñoz (2004) support the findings of Nandy & Choudhuri (2002).…”
Section: Introductionsupporting
confidence: 70%
“…Küker et al (2001) point out: "all recent dynamo models with the observed rotation law are faced with this problem, even when the α effect has been strongly reduced in the polar region by the relation α ∝ sin 2 θ cos θ, as we also did". Nandy & Choudhuri (2002) have recently shown in a brief communication that this problem can be solved by postulating a meridional flow penetrating somewhat deeper than hitherto believed. If the meridional flow goes below the tachocline near the poles, then the strong toroidal field produced within the tachocline at high latitudes is immediately pushed underneath into the convectively stable layers and cannot emerge at the high latitudes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another discovery of helioseismology, meridional circulation of the CZ, lies at the heart of recent modelling of the solar cycle oscillations of the mean field dynamo (e.g. Nandy & Choudhouri 2002). Early indications are that the recent long and low solar minimum has been associated with unusually slow equatorward migration of the deep band on enhanced zonal flow that in previous cycles has been seen prior to the onset of flux eruption to the solar surface (Hill 2008;Phillips 2009).…”
Section: Magnetic Field Effects On Heat Flux In the Solar Convection mentioning
confidence: 99%
“…Computing those physical processes self-consistently would otherwise require costly full 3-D magnetohydrodynamical (MHD) simulations (Cattaneo 1999;Brun et al 2004). Among the various mean field dynamo models, the Babcock-Leighton flux transport dynamo models have recently been the favored ones and have demonstrated some success at reproducing solar observations assuming either an advection or a diffusion dominated regime for the transport of field from the surface down to the tachocline (Dikpati & Charbonneau 1999;Nandy & Choudhuri 2002;Dikpati et al 2004;Chatterjee et al 2004;Charbonneau 2005;Bonanno et al 2005;Jouve & Brun 2007a;Yeates et al 2008).…”
Section: Introductionmentioning
confidence: 99%